Aigel’s song Gas as an anti-war manifesto: Poetical, musical and folklore aspects - Vorontsova, Kristina (Przegląd Wschodnioeuropejski, 2026)
This paper analyzes the song Gas by Aigel Gaisina as a contemporary reinterpretation of the folkloristic genre of lamentations. The core research question addresses how the song utilizes traditional poetics while subverting and deconstructing them to reflect collective trauma and anti-war sentiment following 2022. The theoretical framework combines folkloristic studies with musical analysis, drawing on Baroque symbolism and song studies. Methodologically, the study employs textual analysis, intertextual comparisons, and musical semiotics. The paper argues that Gas incorporates ritualistic syntax, tabooed lexemes, and archetypal imagery, adapting them to a modern context. It highlights the song’s duality, drawing from both Slavic and Tatar lament traditions while rejecting their consolatory functions. Instead, the song portrays death as omnipresent and inescapable. This bleak imagery critiques war, framing it as senseless violence that eradicates hope and humanity. These findings contribute to understanding contemporary folklore-inspired art as a medium for expressing societal despair, political critique, and anti-war messages.